Differential gene expression in roots of sugarcane hybrids provides insights into drought stress tolerance - Garcia, Ana Letycia Basso (2024)
Sugarcane is one of the main crops that contributes to the Brazilian economy. A major challenge for sugarcane breeding programs has been developing cultivars that are more productive and tolerant to adverse environmental conditions, such as drought stresses. Gene expression analysis is an effective way to identify genes involved in drought response and understand how these genes regulate plant physiology under stress. The aim of this study was to identify genes in sugarcane roots that regulate the response to soil water deficit stress and to identify gene expression patterns associated with tolerance to drought. For this, we evaluated gene expression in six commercial sugarcane hybrids (RB867515, RB855113, RB855536, RB92579, SP79-1011, and SP80-3280). Roots were collected from a 2 x 2 factorial experiment in a greenhouse. One of the main factors tested was the effect of water availability in the soil (control treatment and treatment with water deprivation for five days) and the other factor was the effect of genotypes, grouped as susceptible or tolerant to drought. We performed RNA-seq for three biological replicates of roots of each treatment. These sequences were used to assemble a de novo transcriptome, which was functionally annotated and used as a reference to estimate gene expression levels in each sample from a quasi-mapping strategy. We then performed a differential gene expression analysis to identify genes responsive to the main effects of drought stress and cultivar group. Finally, we explored the interaction between these two main effects. We found 1,913 upregulated genes and 1,550 downregulated genes for the main effect of drought stress, showing common responses to stress between the two groups of cultivars. The majority of these genes were related to abiotic stress responses and include kinase precursors, transcription factors, and proteins that confer cellular homeostasis. In addition, we identified 12,939 differentially expressed genes (DEGs) for the main effect of cultivars, suggesting a significant divergence in gene expression between tolerant and susceptible cultivars. These genes are mostly related to biotic stress and the general response to stress. Finally, we identified 412 DEGs that have an interaction between the effects of the treatment and cultivar group, in which more than 86% were induced in tolerant genotypes under drought stress. Many of these genes enriched gene ontologies related to defined biological processes such as: ethylene-activated signaling pathway, negative cytokinin regulation, and cell signaling. Therefore, we conclude that drought tolerance is possibly associated with innate gene characteristics present in tolerant genotypes. Some of these genes are involved in hormonal signaling pathways and are induced in the roots of tolerant cultivars under drought stress. Thus, we suggest an in-depth investigation of the drought tolerance genes that we identified in this work, to better understand the role of each of these genes in regulating drought stress tolerance. These results are valuable in understanding the genetic mechanisms of drought tolerance, which will contribute to better efficiency in the development of new drought-tolerant sugarcane cultivars.